Examining interactions between chronic pain, positive mental health and coping on past-year suicidal ideation in a Canadian sample - Sarah E. Turner; Justin J. Lang; Natalie Doan; Melanie Varin; Wendy Thompson; Raelyne L Dopko (SSM - Mental Health)
Introduction: Chronic pain affects approximately 20% of the Canadian population and is related to increases in suicide-related outcomes. Protective factors for suicidal behaviours are understudied, yet they are an important area of research for promoting mental health and preventing suicide. This study examined the relationship between chronic pain and past-year suicidal ideation and the moderating roles of positive mental health and coping. Methods: Data were from the 2019/20 cycle of the Canadian Community Health Survey, a cross-sectional Canadian survey (n= 64,654). Chronic pain (yes/no), positive mental health (including self-rated mental health (low/high) and community belonging (low/high)), coping (low/high) and past-year suicidal ideation (yes/no) were measured using self-report survey questions. We used weighted logistic regression to assess relationships between chronic pain, self-rated mental health, community belonging, coping, and suicidal ideation adjusting for sociodemographic, mental health and substance use variables. Additive and multiplicative interactions were used to test moderation between chronic pain, positive mental health and coping on past-year suicidal ideation. Results: Experiencing chronic pain was associated with increased odds of suicidal ideation (adjusted odds ratio [aOR] 2.32, 95% Confidence Interval [CI] 1.85- 2.90). High positive mental health and coping were protective factors for suicidal ideation (aORs of 0.13, 0.57 and 0.24, respectively). Additive interactions showed that experiencing chronic pain, along with low positive mental health or coping was associated with a higher odds of suicidal ideation than the sum of the individual associations. There were no significant multiplicative interactions. Conclusion: This study shows that chronic pain is associated with higher odds of suicidal ideation, and the odds were even higher for those who also reported low positive mental health or coping. In addition to facilitating reductions in chronic pain, providing individuals experiencing chronic pain with mental health support and coping skills may protect against suicidal ideation.